Handbook of cultural sports psychology - Jancosek, Natalie; Bisgaard, Christian Højen (Emerald Publishing Limited : Information Age Publishing Inc., 2024)
The desire of this volume is to approach sports and the athletic sphere through Cultural Psychology. The particular focus is on the grounds and necessity of Sports Psychology and the cultural psychological additions to this area.Sports, especially competitive sports and performing arts offer us new arenas for studying and understanding human nature. Thus, the main characters of the chapters of this book are athletes who want to excel and achieve new heights through their personal devotion to their sports. To understand athletes' abilities to reach excellence and to enhance our understanding of the constructive inherent in psychology and thus move beyond the reconstructive idiom in mainstream psychology we propose that sport is a cultural psychological phenomenon - therefore it needs to be studied as such to understand how these competitive sports environments allow the athletes to strive for excellence.This volume depicts the historical development of sport and how this development makes both overt and tacit knowledge available to our meaning-making processes. Complementary, this volume investigates how sport serves as a medium for personal development in the sporting context as well as in everyday life, therefore it was important to elaborate both theoretically and practically on ideas and topics of the individual chapters with the help of the notion of dialogical negotiation of meaning in sport communities.
Keywords: Sports -- Psychological aspects.; Ethnopsychology.; Athletes -- Psychology.; Sports & Recreation -- Sports Psychology.; Sports psychology.; elektronické knihy; electronic books